The Effects of Cleistanthoside A Tetraacetate Synthesis on Acute Toxicity and Bone Marrow Micronucleus in ICR Mice - PUCHADAPIROM, Pranom; HIMAKHUN, Wanwisa; TUCHINDA, Patoomratana; HIMAKOUN, Lakana; KOOMSANG, Thidarat; SUWANNALERT, Prasit (Walailak Journal of Science and Technology (WJST), 2015)
Phyllanthus taxodiifolius Beille is used in traditional medicine in tropical and subtropical areas. Although it has been used as a folk medicine for a long time, studies on its safety have been limited. In this study, the bone marrow micronucleus and oral toxicity of Cleistanthoside A tetraacetate, a modified arylnaphthalide lignan of Cleistanthoside A from the P. taxodiifolius Beille, were evaluated. Imprinting control region (ICR) female mice were orally administered Cleistanthoside A tetraacetate at doses of 250, 500 and 1,000 mg/kg body weight (BW). Signs of toxicity, bone marrow micronucleus, clinical blood chemistry, and histopathological findings were determined after treatment. No mortality was observed in any of the groups. A significant increase in numbers of bone marrow micronucleus, marked elevation of alkaline phosphatase (ALP), blood urea nitrogen (BUN), and creatinine (CRE) were observed in the mice administered with Cleistanthoside A tetraacetate 1,000 mg/kg BW. These results also correlated with the histopathological scoring of liver and kidney cells in ICR mice. The mice administered with Cleistanthoside A tetraacetate 1,000 mg/kg BW had high toxicity in the liver and kidneys. Long term or chronic toxicity should be further studied for safety. doi:10.14456/WJST.2015.68